Uji Organoleptik Produk Olahan Nugget Jagung Yang Ditambahkan Sayuran Di Desa Motilango - Juramang, Risnayanti R; Kadir, Rian; Mukdin, Novita B; Faqih, Ahmad; Tomayahu, Tian (Jurnal Biologi Babasal, 2023)
Abstract: The purpose of this study was to determine the level of product preference through organoleptic tests of corn nuggets which were varied with vegetables. Because this research is experimental in nature using the LSD test to perform organoleptic tests on panelists, the research methodology used in this research is a quantitative approach method. A completely randomized design (CRD) with only one element was used to analyze the research data. Based on the characteristic rating scale, it shows that the sample with a mixture of celery has the most favorable taste based on the respondents' assessment. For texture, respondents preferred nuggets with a mixture of wartel compared to original nuggets and a mixture of celery. In terms of color, the nuggets mixed with celery were the most liked by the respondents. In Aroma, based on the respondent's assessment, the carrot mixture has a scent that the respondent likes. Samples with a mixture of celery have the most preferred taste based on the respondents' assessment. For texture, respondents preferred nuggets with a mixture of wartel compared to original nuggets and a mixture of celery. In terms of color, the nuggets mixed with celery were the most liked by the respondents. In Aroma, based on the respondent's assessment, the carrot mixture has a scent that the respondent likes.